Manajemen Kepala Desa Dalam Merevitalisasi Kegiatan Keagamaan Di Desa Bandar Pasir Mandoge Kabupaten Asahan - Panjaitan, Diki Hamdani; Kustiawan, Winda (AL-FIKRA, 2025)
This study aims to ensure that religious activities can continue to develop and provide maximum benefits for the social and spiritual welfare of the village community. This type of research is qualitative research with the aim of understanding the phenomenon in depth through interpretation and descriptive analysis. The informant of this study is Mr. Irwadi as the Head of Bandar Pasir Mandoge Village. The data collection procedures used in the study are: first, interviews and second is Documentation. The stages in data analysis are Checking and organizing. The results of the study indicate that religious activities in Bandar Pasir Mandoge Village include Routine Religious Studies, Commemoration of Islamic Holidays (PHBI) and Musabaqoh Tilawati Qur'an, and Managerial activities include planning, organizing, mobilizing/Planning, controlling and evaluating.